ANALISIS SOSIOLOGI HUKUM (Studi Terhadap Tindak Pidana Kekerasan Dalam Rumah Tangga Di Kabupaten Bone ) - Risman Risman (Jurnal Syariah Hukum Islam, 2019)
ABSTRACT In order to prevent, protect victims, and take action against perpetrators of domestic violence, States and communities shall exercise the prevention, protection and prosecution of perpetrators in accordance with the Pancasila philosophy and the 1945 Constitution of the State of the Republic of Indonesia. Research on Juridical Analysis of Domestic Violence in Bone District is a type of normative legal research (dokmatic) and sociological legal research (empirical) then the approach used is the juridical approach of normatis and sociology. The implementation of the Law of the Republic of Indonesia Number 23 Year 2004 on the Elimination of Domestic Violence in Bone Regency has not been implemented properly because there are still many wives not understand the Law regulating the crime of violence in the household even there are wives who do not want reported the case because it still considers that it is the household's own affairs and if reported to the authorities will bring a family disgrace because already many people know about the violence committed by her husband. The fact that there has been an increase in cases of domestic violence against the community in Kabupaten Bone, there are several factors such as legal awareness, moral factors, environmental factors, educational factors and law enforcement factors that influence the implementation of the Law of the Republic of Indonesia Number Law No. 23 of 2004 on Elimination of Domestic Violence becomes less effective